The Formation of the Professional Culture of Future Teachers of Technology (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
this article analyzes the pedagogical and technological foundation in the format of the professional culture of future teachers of. The significance of tea and munching rolan professional activities in the culture is revealed. The grade will also be based on the development of the professional competencies metho pair of modern educational technologies. The article will cover the following issues, the components of the professional culture and its format factor of, rolan the tea and munching metho innovative technologies, strategies for the development of professional ethics in teaching and student culture.